Comparison of efficiency of parasitological methods with Ag-ELISA in Trypanosoma evansi infected crossbred calves - SINGH, A; CHAUDHRI, S S (The Indian Journal of Animal Sciences, 2014)
The efficiency of parasitological methods including wet blood film (WBF), microhaematocrit centrifugation technique (MHCT) and mouse sub-inoculation test, (MSI) was compared with the polyclonal antibody based indirect antigen detection enzyme immunoassay (Ag-ELlSA) in 8 to 12 months old crossbred male calves experimentally infected with Trypanosoma evansi. The parasitaemia was found in 3 crossbred calves on day 3 post infection (PI) and in remaining calf on day 7 PI with MHCT and WBF. The antigenaemia was detectable with Ag- ELISA for the first time in all infected calves on day 7 PI. Thereafter, antigenaemia was detectable throughout the post infection (PI) periods while parasitaemia continued to be detected at irregular periods. Ag-ELISA was more sensitive than parasitological tests in obscrving the true epidemiological status of trypanosomos is in cattle.